Reverse logistics challenges in remanufacturing of automotive mechatronic devices - Sundin, Erik; Dunbäck, Otto (Journal of remanufacturing, 2013)
The remanufacturing industry as a whole and the automotive sector in particular have, over the years, proven to be beneficial to the environment and economically lucrative to the companies involved as well as to their customers. However, remanufacturing is associated with complicating characteristics, not least to mention the process of core acquisition. The automotive industry is one of the earliest adapters of remanufacturing. Parts like engines, brake calipers and servo pumps are common targets for remanufacturing. Modern cars also have several embedded computers, often referred to as electronic control units that communicate, share information and verify each other over a Controller Area Network (CAN) bus. Due to their high value and an increasing trend in the amount of CAN bus mechatronic devices, interest in their remanufacture is growing. Previous research has shown that it is preferable that the remanufacturer is an original equipment manufacturer (OEM), or has a close relation to the OEM, in order to achieve a well-performing remanufacturing business. In the automotive industry, there are many small and medium-sized enterprises (SMEs) that perform remanufacturing; for these enterprises, the challenges to have a profitable business are even harder. This is because the OEMs will not release any information on the communication parameters and therefore will not support the independent remanufacturing business. As a consequence, the independent remanufacturers, often SMEs, have to perform substantial reverse engineering. This paper presents a qualitative research study, based on interviews at SMEs regarding challenges linked to the reverse logistics of SMEs remanufacturing and trading used automotive mechatronic devices, to identify specific challenges concerning the collection phase of automotive mechatronic remanufacturing. Challenges previously identified by researchers are confirmed, additional challenges within the collection phase are recognized, and challenges expected to arise when remanufacturing and trading automotive electronic CAN bus mechatronic devices are identified. The major concern for the involved companies when commencing future challenges is the handling, transportation and storing of cores. Even though the cores today mainly consist of mechanical devices, these challenges are still present; they are expected, however, to become even more crucial when cores contain a higher degree of mechatronic devices.